Elevated α-hydroxybutyrate dehydrogenase is associated with in-hospital mortality in non-ischemic dilated cardiomyopathy - Li, Xinyi; He, Wenfei; Zhang, Xiaonan; Shu, Fen; Liu, Yaoxin; Tan, Ning; Jiang, Lei (Frontiers in Cardiovascular Medicine, 2022)
Background Previous Study Found That Implantation of a Cardioverter-Defibrillator Likely Caused a Worse Prognosis in Older Patients With non-Ischemic Systolic Heart Failure. This Suggests That More Precise Risk Stratification Is Needed in Elderly Patients. We Conducted a Retrospective Study to Evaluate the Association of α-Hydroxybutyrate Dehydrogenase (α-HBDH) With Mortality During Hospitalization in Elderly Patients With non-Ischemic Dilated Cardiomyopathy (NIDCM). Methods 1,019 Elderly Patients (age ≥60 Years) Diagnosed With NIDCM Were Retrospectively Enrolled From January 2010 to December 2019. Univariate and Multivariate Analyses Were Showed to Explore the Relationship Between α-HBDH and in- Hospital Death. Results Patients in elevated α-HBDH group (>182 U/L) had a longer hospital stays and higher in-hospital mortality. Univariate logistics regression analysis showed that elevated α-HBDH was significantly related to mortality (OR: 7.004, 95% CI: 3.583–13.693, p < 0.001). Receiver operator characteristic (ROC) curve analysis reflected that α-HBDH levels had excellent predictive power for in-hospital death (AUC = 0.810, 95% CI: 0.745–0.876, p < 0.001). After adjustment of age, serum creatine, albumin and LVEF, multivariate regression analysis validated the association of elevated α-HBDH with increased risk of in-hospital death (p < 0.05). Conclusions Elevated α-HBDH level is significantly related to in-hospital mortality in older patients with NIDCM.